Prediction of Drought Severity Using Model-Based Clustering. (23rd July 2021) - Niaz, Rizwan; Hussain, Ijaz; Zhang, Xiang; Ali, Zulfiqar; Elashkar, Elsayed Elsherbini; Khader, Jameel Ahmad; Soudagar, Sadaf Shamshoddin; Shoukry, Alaa Mohamd
Abstract : Drought is a common climatic extreme that frequently spreads across large spatial and time scales. It affects living standard of people throughout the globe more than any other climate extreme. Therefore, the present study proposed a new technique, known as model-based clustering of categorical drought states sequences (MBCCDSS), for monthly prediction of drought severity to timely inform decision-makers to anticipate reliable actions and plans to minimize the negative impacts of drought. The potential of the proposed technique is based on the expectation-maximization (EM) algorithm for finite mixtures with first-order Markov model components. Moreover, the proposed approach is validated on six meteorological stations in the northern area of Pakistan. The study outcomes provide the basis to explore and frame more essential assessments to mitigate drought impacts for the selected stations.